A novel open‐tubular capillary electrochromatography using carboxymethyl‐β‐cyclodextrin functionalized gold nanoparticles as chiral stationary phase. Issue 5 (27th December 2019) - Zhang, Chenning; Qu, Jialin; Lv, Xiaoyuan; Zhang, Jianbin; Fang, Linlin
Abstract: Enantioselective open tubular capillary electrochromatography with carboxymethyl‐β‐cyclodextrin conjugated gold nanoparticles as stationary phase was developed. This novel open tubular column was fabricated through layer‐by‐layer self‐assembly of gold nanoparticles on a 3‐mercaptopropyl‐trimethoxysilane‐modified fused‐silica capillary and subsequent surface functionalization of the gold nanoparticles through self‐assembly of 6‐mercapto‐β‐cyclodextrin. The 6‐mercapto‐β‐cyclodextrin was firstly synthesized and determined by extensive spectroscopic data. Scanning electron microscopy, energy dispersive X‐ray analysis spectroscopy, and electroosmotic flow experiments were carried out to characterize the prepared open tubular column. Then, the separation effectiveness of the open tubular column was verified by two pairs of ɑ‐tetralones derivatives enantiomers and two pairs of basic drug enantiomers (tramadol hydrochloride and zopiclone) as mode analytes. Factors that influence the enantioseparation were optimized, and under the optimized conditions, satisfactory separation results were obtained for the four enantiomers: compound A, compound B, tramadol hydrochloride, and zopiclone with resolutions of 3.79, 1.56, 1.03, 1.60, respectively. For the combination of gold nanoparticles and negatively charged carboxymethyl‐β‐cyclodextrin, the open tubular column exhibited wider separation range for neutral and basic drugs. Moreover, the repeatability and stability of the column were studied through the run‐to‐run and day‐to‐day investigations.